Leksikon dan Distribusi Bahasa Melayu Riau Melalui Fitur Fonologi di Kabupaten Kampar - Yani, Juli; Puspita, Alvi; Ridwan, Ridwan; Syamsidar, Raja (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
The lexicon and distribution of Riau Malay emerged because of causes that are closely related to language changes observed in certain elements found in the variety of dialects, regional boundaries, number of speakers, residence, identity and cultural pride, and economic conditions. The purpose of this study was to determine (1) the lexical form of phonology and (2) the geographical distribution of phonological forms that experience variations in Riau Malay in Kampar Regency. This research uses a descriptive method with listening, interviewing, recording, and recording techniques. The methods and analytical techniques used are the padan method and the banding technique. This research was conducted at nine observation points in Kampar Regency. The sample of informants at each observation point amounted to one person. The research instrument used for the interview was a list of questions containing 441 questions. The results of this study are based on its realization: the determination of phonetic innovations based on the discovery of variants that show a phonotactic change from the original variant at the Riau Malay observation point in Kampar Regency. Its geographical phonological distribution is based on observation points and the results of data phenomena in the field that often experience dispersal at observation points (1), (2), (3), (8), and geographically.